KISRUH LAPORAN KEUANGAN : BAGAIMANAKAH KINERJA KEUANGAN PT GARUDA INDONESIA TBK? - Nuri, Listika; Andriani, Sri (Jurnal TAMBORA, 2021)
Garuda Indonesia Tbk is the best airline company in Indonesia. However, the chaos in Garuda Indonesia Tbk's financial statements that occurred in 2018 caused a decline in financial performance which was reflected in the company's stock price. This study was conducted to determine the financial performance of Garuda Indonesia Tbk seen from the effect of the liquidity ratio (current ratio) on the company's stock price with the profitability ratio (return on assets) as an intervening variable. The results showed that the liquidity ratio had an effect on Garuda Indonesia's stock price. However, the liquidity ratio does not affect the company's profitability. In addition, the profitability ratio also has no significant effect on stock prices. Finally, the profitability ratio is not able to mediate the effect of the liquidity ratio on the stock price of Garuda Indonesia Tbk.